Difficulties of interpreting Borrelia Serology in patients with Uveitis - Mackensen, Friederike; Zimmermann, Stefan; Alle, Werner; Max, Regina; Jakob, Eva; Becker, Matthias D.; Thiemeyer, Dorothea (Ocular immunology and inflammation, 2011)
Purpose: We aimed to review all uveitis patients with a positive Borrelia serology to evaluate positve results in uveitis subtypes. Further we wanted to test a self-assembled Interferon gamma release assay (IGRA) as a possible supplement method in these patients.Methods: Patients where serology for Borrelia was ordered from September 2005 to May 2008, were identified by database search. Patients with positive results in ELISA and Western Blot were retested by a self-assembled IGRA. Bayes Theorem was applied.Results: Testing for Borrelia was ordered for 184 patients. 18 patients (9,8%) showed positive results. 11 were positive for IgG (5,9 %), 3 were positive for IgG and IgM (1,6 %) and 4 for IgM (2,1%). Applying Bayes Theorem, we calculated a posttest-probability of 9% in case of a positive test result. 16 of the 18 patients were retested by IGRA. None of them showed a positive result.Conclusions: A positive serology with uveitis as the only clinical symptom is not sufficient to confirm Borreliosis as 5,9 % of patients with uveitis and a positive IgG serology correspond to the normal spread of Borrelia in the population. Looking at posttest-probability shows a lot of false-positive test results when testing all uveitis patients for Borrelia routinely.
Gesehen am 24.11.2022